The idea of history with lectures 1926 -1928 - Collingwood, R. G. (Robin George), 1889-1943.; Dussen, W. J. van der.; American Council of Learned Societies (Oxford ; New York : Oxford University Press, 1994)
"The Idea of History is the best-known work of the great Oxford phil osopher, historian, and archaeologist R.G. Collingwood. This important work examines how the idea of history has evolved from the time of Hero dotus to the twentieth century, and offers Collingwood's own view of wh at history is. This revised edition has a substantial new introduction which discusses how scholars have responded to Collingwood's classic ov er the last fifty years"--Publisher's site.
Characteristics of Christian historiography -- Medieval historiograp hy -- The Renaissance historians -- Descartes -- Cartesian historiograp hy -- Anti-Cartesianism : Vico -- Anti-Cartesianism : Locke, Berkeley, and Hume -- The Enlightenment -- The science of human nature -- pt. III . The threshold of scientific history. Romanticism -- Herder -- Kant -- Schiller -- Fichte -- Schelling -- Hegel -- Hegel and Marx -- Positivi sm -- pt. IV. Scientific history. England. Bradley ; Bradley's successo rs ; Late nineteenth-century historiography ; Bury ; Oakeshott ; Toynbe e -- Germany. Windleband ; Rickert ; Simmel ; Dilthey ; Meyer ; Spengle r -- France. Ravaisson's spiritualism ; Lachelier's idealism ; Bergson' s evolutionism ; Modern French historiography -- Italy. Croce's essay o f 1893 ; Croce's second position : the logic ; History and philosophy ; History and nature ; Croce's final position : the autonomy of history -- pt. V. Epilegomena. Human nature and human history [1936] -- The his torical imagination [1935] -- Historical evidence [1939] -- History as re-enactment of past experience [1936] -- The subject-matter of history [1936] -- History and freedom [1939] -- Progress as created by histori cal thinking [1936].
Originally published: Oxford : Clarendon Press, 1993. With new intro duction.
Includes bibliographical references and index.
Electronic text and image data.
Keywords: History -- Philosophy; Historiography